A Content Analysis of Gendered Research in the Canadian Journal of Counselling and Psychotherapy - Bedi, Robinder P.; Young, Courtney N.; Davari, Jaleh A.; Springer, Karen L.; Kane, Daniel P. (Canadian Journal of Counselling and Psychotherapy, 2016)
There is increased awareness of but limited quantification of the lack of published scholarship about boys and men in counselling. We conducted a content analysis on articles published in the Canadian Journal of Counselling and Psychotherapy from 2000 to 2013 to examine gender differences in research participants and to explore the topics published. After reviewing 293 articles, we found that female-topic-specific articles outnumbered male-topic-specific articles by 3:1 and research studies based on exclusively female client/ student samples outnumbered those based on exclusively male samples by about 4:1. When examining only gender-specific articles that were intentionally seeking to look at a particular gender—not including the four articles in Vol. 46, No. 4 (2012), the special issue on boys/men—the ratio of female-specific articles to male-specific articles is about 5:1; for research studies that ratio is about 15:1. This leaves clinicians with a small Canadian research base from which to provide gender-sensitive and evidence-based interventions with boys/men.